Comparing Soft-Scape Quality Standard Between Malaysia And Developed Countries - Ibrahim, Roziya (2009)

(untitled)
The Malaysia government‟s vision towards a “Garden Nation” in year 2005, followed by „The Most Beautiful Garden Nation‟ by the year 2020 has boosted rapidly the landscape development throughout the country. However, as reported by the Malaysia Construction Industry Development Board (CIDB, 2000), these massive and hasty developments have led to a devastating compromise in quality. This issue is critical in landscape development, as currently, there is no specific quality standard to monitor and control the quality of soft-scape materials and works. Landscape projects are it is a quite unique form of construction that blend the inert materials with the living plants, or commonly known as the hard-scape and the soft-scape, within the environment. Based on the building industry practice, the quality of the hard-scape is specific and codified. For soft-scape, however, there is a wide range of subjectivity with regard to the quality of the soft-scape materials and works. Therefore, there is a need to evaluate the quality standard of soft-scape as it is an important document in specifying the quality aspect of the landscape development in Malaysia. This research used a mixed-method approach. It adopted a constant comparative method to explore the similarities and differences between the quality standard of soft-scape practices in Malaysia and those in the USA and UK. Tender documents and the soft-scape specifications together with data from the interviews with local professional landscape personnel were the two main important data sources to identified the issues and problems related to the quality standard of soft-scape in this country. It also verifies the strength and weaknesses of the present soft-scape practices in Malaysia. Site observations at the nurseries and at the landscape construction site on the other hand helped to validate the written documents. These findings identified the insufficient standard to monitor and control the quality of soft-scape materials and works in this country. At the end of the research, recommendations were provided for improving the quality standard of soft-scape materials and works that represent the overall landscape development towards sustainability in Malaysia.